The Impact Of Cyberbullying On Adolescents On Social Media - Romy Maranatha Ginting; Muhammad Arif Sahlepi (International Journal of Sociology and Law, 2024)
The development of social media networks is extraordinary, with very easy access and unlimited friendships so that all groups regardless of social status ranging from old, young, and even children are so enthusiastic in using social media especially teenagers. Social networks are also used as a place for emotional outbursts, and it is not uncommon to express anger in the form of insults or insults which are often referred to as cyberbullying. The ITE Law provides legal protection for victims of criminal acts of cyberbullying as an effort to protect the law which is interpreted as the recognition and guarantees provided by the law in relation to human rights. Legal protection is a "condition sine quanon" law enforcement is a manifestation of the function of the law as its aim. is to prevent disputes. The purpose of writing is to determine the impact of cyberbullying on adolescents on social media. The method used is literature review using articles and journals from 2016 to 2020 obtained from the Google Scholar electronic database. The results of various studies show that cyberbullying on adolescents on social media has a huge impact that affects all aspects of life from psychological, physical, and social aspects. The impact of cyberbullying that is felt is not only the victim, but the perpetrator, perpetrator and victim will also have an impact.